2013
DOI: 10.1140/epjd/e2013-40259-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical pumping of a lithium atomic beam for atom interferometry

Abstract: We apply optical pumping to prepare the lithium beam of our atom interferometer in a single hyperfine-Zeeman sublevel: we use two components of the D1-line for pumping the 7 Li atoms in a dark state F, mF = +2 (or −2) sublevel. The optical pumping efficiency has been characterized by two techniques: state-selective laser atom deflection or magnetic dephasing of the atom interferometer signals. The first technique has not achieved a high sensitivity, because of a limited signal to noise ratio, but magnetic deph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
(81 reference statements)
1
17
1
Order By: Relevance
“…The m F value measured on an axis parallel to the local magnetic field is conserved along the atom propagation, if the condition for an adiabatic transport is fulfilled and our measurements of the pumping efficiency rule out any Majorana spin-flip of the optically pumped atoms along their propagation. We have characterized the pumping efficiency by an atom interferometric method and we have found that the pumped sublevel has a fraction of the total population near 95 ± 5% [24]. Our results are recalled in table 3.…”
Section: /(Vmentioning
confidence: 87%
See 1 more Smart Citation
“…The m F value measured on an axis parallel to the local magnetic field is conserved along the atom propagation, if the condition for an adiabatic transport is fulfilled and our measurements of the pumping efficiency rule out any Majorana spin-flip of the optically pumped atoms along their propagation. We have characterized the pumping efficiency by an atom interferometric method and we have found that the pumped sublevel has a fraction of the total population near 95 ± 5% [24]. Our results are recalled in table 3.…”
Section: /(Vmentioning
confidence: 87%
“…Using eq. (3) and assuming B mot parallel to e B , we predict an AC phase slope |∂ϕ AC /∂V | = (8.57 ± 0.05) × 10 −5 rad/V with an uncertainty due to the p-3 Table 3: The measured population P (F = 2, mF ) after optical pumping for different atom velocities vm [24].…”
Section: /(Vmentioning
confidence: 96%
“…The longitudinal width of the ensemble is assumed to be 50 μm in order to reduce the effect of group-velocity mismatch between the laser pump and electron probe pulses. The density of the lithium atom ensemble is assumed to be 10 10 cm −3 [63], so that the projected area density of the lithium atom gas is ρ(b) = 5.0 × 10 7 cm −2 .…”
Section: Simulation Detailsmentioning
confidence: 99%
“…2(b)). Optical pumping on the D 1 line therefore avoids the slightly off-resonant transitions ubiquitous on the D 2 line [39]. In each of the six 3D MOT beams, we use 1.5 mW of D 2 MOT repump light to recover atoms that decay to |F = 1 .…”
mentioning
confidence: 99%